Enkola ennungi ez’okunoonya akatale k’amatooke - Kikulwe, Enoch Mutebi; Ajambo, Susan; Tushabe, H.; Baligeya, E.; Nalunga, Asha; Nowakunda, K.; Batte, Michael; Gibert, Olivier; Mayanja, S.; Naziri, D. (International Potato Center, 2016)
This protocol is designed to support farmers to improve the quality of their bananas in the field and the postharvest practices in a bid to facilitate access to better prices and niche markets. The protocol is organized into three sections: Section 1 Good Agricultural Practices (GAP); Section 2: Proper Harvest and Handling Practices and Section 3: Good Marketing Practices (GMP).